Cranial morphology and phylogenetic analysis of Cynosaurus suppostus (Therapsida, Cynodontia) from the Upper Permian of the Karoo Basin, South Africa. - Van den Brandt, M. (2018)
Non-mammaliaform cynodonts are an important fossil lineage which include the ancestors of mammals and which illustrate thegradual evolution of mammalian characteristics. The earliest cynodonts (?basal cynodonts?) are known from the late Permian.Cynosaurus suppostus is the second most abundant basal cynodont from the late Permian of the Karoo Basin of SouthAfrica, but is poorlystudied, with the most recent description of this taxon being 50 years old. Since then, several important new specimens of this specieshave been collected, meriting a thorough description of its cranial anatomy and exploration of its interspecific variation. Here wepresent a comprehensive description of the cranial morphology of Cynosaurus suppostus, producing an updated diagnosis for thespecies and comparisons amongst basal cynodonts. Cynosaurus is identified by three autapomorphies amongst basal cynodonts: asubvertical mentum on the anterior lower jaw; a robust mandible with a relatively high horizontal ramus; and the broadest snout acrossthe canine region, representing up to 31.74% of basal skull length. One of the new specimens described here preserves orbital scleralossicles, structures rarely preserved in non-mammaliaform cynodonts. Cynosaurus is now only the third cynodont in which scleralossicles have been reported.Anupdated phylogenetic analysis of basal cynodont interrelationships recovered Cynosaurus suppostus as amember of the Galesauridae in only two of 16 most parsimonious trees, providing poor support for its inclusion in that family. Themajority of known Cynosaurus specimens were collected in a geographically restricted area approximately 150 kilometres in diameter.Most specimens have been recovered from the latest Permian Daptocephalus Assemblage Zone, with only two specimens known fromthe older Cistecephalus Assemblage Zone.